Exercise training in pulmonary arterial hypertension - Dalla Vecchia, Laura Adelaide; Bussotti, Maurizio (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Pulmonary arterial hypertension (PAH) is characterized by a continuous increase in pre-capillary pulmonary vascular resistance (PVR) with a progressive reduction of cardiac output (CO). Similar to what occurs in left heart failure (HF), this represents the initial phase of a syndrome characterized by the progressive development of dyspnea and fatigue with increasing deterioration of exercise tolerance. Although the therapies introduced in the last two decades have determined a significant improvement of the clinical conditions of PAH patients, they have a little impact on exercise capacity and prognosis. However, as previously demonstrated for HF, recent pilot studies have reported that physical and respiratory rehabilitation may have a specific role in the management of PAH. Despite potential risks, so far all studies agree that exercise training (ET) improves exercise capacity, quality of life (QoL), muscle function and pulmonary circulation. We will review the pathophysiological mechanisms underlying the functional incompetence of PAH patients, the effects of ET on clinical and functional parameters, the selection criteria for inclusion of patients in a training program, the suggested monitoring of beneficial effects or possible side effects induced by ET. Finally, we discuss of the possible exercise induced amelioration of prognosis in PAH.